COVID-19 Anosmia Reporting Tool: Initial Findings - Kaye, Rachel; Chang, C W David; Kazahaya, Ken; Brereton, Jean; Denneny, 3rd, James C (Otolaryngology-head and neck surgery, 2020)
There is accumulating anecdotal evidence that anosmia and dysgeusia are associated with the COVID-19 pandemic. To investigate their relationship to SARS-CoV2 infection, the American Academy of Otolaryngology-Head and Neck Surgery developed the COVID-19 Anosmia Reporting Tool for Clinicians for the basis of this pilot study. This tool allows health care providers to confidentially submit cases of anosmia and dysgeusia related to COVID-19. We analyzed the first 237 entries, which revealed that anosmia was noted in 73% of patients prior to COVID-19 diagnosis and was the initial symptom in 26.6%. Some improvement was noted in 27% of patients, with a mean time to improvement of 7.2 days in this group (85% of this group improved within 10 days). Our findings suggest that anomia can be a presenting symptom of COVID-19, consistent with other emerging international reports. Anosmia may be critical in timely identification of individuals infected with SARS-CoV2 who may be unwittingly transmitting the virus.